The interface between internal and external audit in the Australian public sector - Pilcher, Robyn; Gilchrist, David; Singh, Harjinder; Singh, Inderpal (Wiley-Blackwell Publishing Asia, 2013)
This study seeks to answer the research question ‘using reliance as the pivotal consideration, what factors determine the efficient and effective interrelationship between internal and external audit?’, within the context of the Australian public sector. A qualitative approach, framed within agency theory, was adopted using a case study and structured interviews. Findings included factors supporting prior literature as well as some unique to the research described here. As a result, this article makes a contribution to the literature examining public sector internal and external audit interrelationships as well as the literature on police audit and performance. It also has practical implications for both the case study site and similar organisations throughout the world.